An Assessment of Environmental Awarness:The Role of Ethic Education - Indri Murniawaty (JSSH (Jurnal Sains Sosial dan Humaniora), 2018)
Environmental damage that occurred in Indonesia in the last three decades is due to human behavior by exploiting and depleting the universe in order to meet the interests and needs of human’s life. The objectives of this research were (1) to find out the direct effect of the students’environmental knowledge towards the environmental awareness, (2) to find out the indirect effect of the students' environmental knowledge towards the environmental awareness through ethics, (3) to find out the direct effect of student's ethics on environmental awareness. The sample of this research was the students of economic education who hadlearned the subject of environmental education. The researcher used a quantitative approach with explanatory research design to explain the state of each variable. Two things that contribute to environmental awareness were ethics and environmental knowledge. The results of this study showed that environmental and ethical knowledge significantly influenced environmental awareness. The environmental knowledge will shape students' attitudes and ethics towards the environment.